PEMBUATAN SOAL-SOAL LATIHAN INTERAKTIF MENGGUNAKAN COURSE LAB DENGAN PENDEKATAN SCIENTIFIC PADA MATERI GERAK LURUS KELAS X SMA - Mutia Yussavel Navis; Festiyed Festiyed; Yenni Darvina (Universitas Negeri Padang, 2017)
A research has been done in order to produce a valid, practical and effective interactive practice questions using of course lab with a scientific approach to the material grade X SMA Straight Motion. The research done isone of Research and Development (R&D), but the steps R&D is done only until the seventh step. Such steps are to recognize the potential and problems, gather information, product design, design validation, the revised design, product testing, and product revision. As research objects are interactive practice questions using course lab with a scientific approach to the subject matter of Straight Motion and testing are students of class X, SMAN 7Padang. The results showed manufacture interactive practice questions using the course lab with a scientificapproach to the material grade X SMA Straight Motion very valid by the validity of 86.25%. The test results of practicality in the aspect of practicality interactive practice questions using the course's lab with practical scientific approach with the practicalities of value to the results of teacher responses was 80% and for the results of the learner response is 79.76%. While the results of the effectiveness of interactive practice test questions using the course's lab with an effective scientific approach Characterized by an Increase in physics learning outcomes of students, Obtained gain score at 0.51 Categorized as moderate